Effects of CEO Duality, Board Independence, Ownership Concentration, Company Age on Profit Persistence and Firm Value: An Empirical Study of Manufacturing Companies in West Java, Indonesia - Maromi Merlin Mbate; Sutrisno (The Es Accounting And Finance, 2023)
This research examines the dual effect of CEO, board independence, ownership concentration, and company age on earnings persistence and firm value in manufacturing companies in West Java, Indonesia. The study conducted a survey of 78 manufacturing companies in West Java in 2022. The results show that CEO duality has a negative effect on earnings persistence, while board independence has a positive effect on earnings persistence. Ownership concentration has no significant effect on earnings persistence, and company age has a positive effect on earnings persistence. In addition, board independence and company age have a positive effect on firm value, while CEO duality and ownership concentration have no significant effect on firm value. These findings suggest that companies with separate CEO and board chairman positions and higher board independence are more likely to have persistent earnings and higher firm value. The study also implies that company age plays an important role in determining earnings persistence and firm value.